2019
DOI: 10.1590/0370-44672018720021
|View full text |Cite
|
Sign up to set email alerts
|

Solar photovoltaic energy applied to ferroalloy industry

Abstract: The Brazilian ferroalloy industry faces a highly competitive scenario in the foreign market. Among the key factors to determine the price of its products, electric energy stands out as one of the main inputs. So, the possibility of energy being unavailable or having high prices causes a direct impact in the ferroalloy chain. On the other hand, the renewable energy market, especially the solar photovoltaic (SPV) energy shows extensive growth due to technological advances and recent regulation. Connecting both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…A participação da energia solar na matriz energética brasileira ainda é pequena, mas o país está, aos poucos, tomando conta da sua relevância. Segundo Silva et al (2019) a produção de eletricidade utilizando sistemas fotovoltaicos apresenta benefícios ambientais bastantes significativos e em termos de segurança energética, sendo que os dispositivos utilizados para conversão de radiação solar em energia elétrica são de fácil aplicação, não produzem ruídos e tampouco elementos poluentes durante sua operação. De acordo com Souza et al (2019), o Brasil apresenta condições naturais favoráveis para a geração de energia elétrica a partir de fonte solar, visto que o país possui níveis de irradiação bem maiores que outros países, onde os projetos para aproveitamento desse tipo de energia são largamente disseminados, como Alemanha, França e Espanha.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A participação da energia solar na matriz energética brasileira ainda é pequena, mas o país está, aos poucos, tomando conta da sua relevância. Segundo Silva et al (2019) a produção de eletricidade utilizando sistemas fotovoltaicos apresenta benefícios ambientais bastantes significativos e em termos de segurança energética, sendo que os dispositivos utilizados para conversão de radiação solar em energia elétrica são de fácil aplicação, não produzem ruídos e tampouco elementos poluentes durante sua operação. De acordo com Souza et al (2019), o Brasil apresenta condições naturais favoráveis para a geração de energia elétrica a partir de fonte solar, visto que o país possui níveis de irradiação bem maiores que outros países, onde os projetos para aproveitamento desse tipo de energia são largamente disseminados, como Alemanha, França e Espanha.…”
Section: Introductionunclassified
“…Os resultados obtidos pelos autores indicam que, devido o constante aumento na demanda de energia desde 2013, apenas 2% da energia deve ser fornecido por termelétricas, a combinação entre energia hidrelétrica e fotovoltaica apresentou um cenário ideal com percentual de 37%, 9% de energia eólica e 50% de geração de energia hidrelétrica. Em um cenário apenas hidrotérmico o risco de déficit energético aumenta dez vezes e a produção de energia térmica quatro vezes mais Silva et al (2019). visando reduzir os custos dos produtos comercializados por uma industria de ferroligas para que a empresa obtenha maior competitividade no mercado externo, os autores desenvolveram um estudo de uma simulação de uma usina fotovoltaica com a finalidade de reduzir os gastos com eletricidade.…”
unclassified
“…Uganda has developed a study in the industrial sector, with 36 industries, focused on the inclination and the surface of photovoltaic solar plants [21]. In Reference [22] it is analyzed the viability of integrated photovoltaic systems in industrial buildings in Greece while [23] shows that the investment in photovoltaics in the industrial sector of ferroalloys in Brazil has good appeal from the financial market point of view. Moreover, it has been shown that incorporating photovoltaic systems for energy supply can make the production of this industry suffer no interruption.…”
Section: Introductionmentioning
confidence: 99%
“…Not only is the usage of solar energy increasing for low voltage consumption, such as houses, it has also been used in industries. Silva et al (2019) analyses the possibility of usage of photovoltaic power plants as the main source in the production of ferroalloy in industries to meet its energy demands, since the unavailability and high costs of energy have a significant impact in the ferroalloy chain. Mekhilefa et al (2011) shows that PV energy has been used for numerous industrial applications such as traffic lights, telecommunications and geographical-position systems for the last 20 years for complementing the energy demand or for reducing the production and maintenance costs of industry applications.…”
Section: Introductionmentioning
confidence: 99%